2011
DOI: 10.1093/ije/dyr172
|View full text |Cite
|
Sign up to set email alerts
|

The inverse relationship between alanine aminotransferase in the normal range and adverse cardiovascular and non-cardiovascular outcomes

Abstract: In three independent populations, ALT in the normal range displayed an inverse relationship with total mortality, cardiovascular events and non-cardiovascular events in middle-to-older aged subjects without evidence of clinically significant liver damage, independent of traditional cardiovascular and other risk factors. These findings indicate that the relationship between ALT and clinical outcomes is more complex than generally appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 26 publications
7
55
5
Order By: Relevance
“…The same study reported that AST showed no association with CVD and that ALT was inversely associated with CVD (7). Ford et al also found an inverse relationship between ALT levels in the normal range and adverse cardiovascular and noncardiovascular outcomes (15). Although the present study revealed an inverse association between ALT and 10-year CVD risks in men, the results for women based on the applied tools and risk levels were inconsistent.…”
Section: Discussioncontrasting
confidence: 75%
“…The same study reported that AST showed no association with CVD and that ALT was inversely associated with CVD (7). Ford et al also found an inverse relationship between ALT levels in the normal range and adverse cardiovascular and noncardiovascular outcomes (15). Although the present study revealed an inverse association between ALT and 10-year CVD risks in men, the results for women based on the applied tools and risk levels were inconsistent.…”
Section: Discussioncontrasting
confidence: 75%
“…This exclusion may also at least partly explain the paradoxical associations between ALT and GGT and mortality observed. Despite this, our data set is consistent with multiple equivalent publications where higher ALT has been excluded in order to avoid the inclusion of individuals with significant liver disease [5,51,52]. Other weaknesses of our analysis include the lack of data for alcohol consumption in grams per week, although this is a notoriously difficult measure to quantify accurately [53], and also the possible inadequate period of follow-up to see the effects of an adverse metabolic profile that may be seen at higher levels of ALT.…”
Section: Accepted M Manuscriptsupporting
confidence: 53%
“…A previous authoritative review 1 indicated that elevated ALT might predict higher mortality in a general population; however, this opinion might be questionable, especially in old adults. Inverse relationships between ALT activity and mortality were observed in several studies focused on older population 57, 99, 100, and this opinion was confirmed by subsequent meta-analysis 101. Dong et al 11, 13 raised the concept that ALT activity might be influenced by accelerated aging and frailty in older adults independent of its traditional role in screening liver function.…”
Section: Several Concerns That Clinicians Should Raisementioning
confidence: 86%
“…A randomized controlled trial (RCT) indicated that the estimated odds ratios (ORs) of ALT elevation in active treatment groups (including acetaminophen, hydromorphone+acetaminophen, morphine+acetaminophen, and oxycodone+acetaminophen) were 2.57-3.08 compared to the placebo group involving 343 healthy participants, even at the recommended dose 56. Another commonly used medication, statins, also causes mild ALT elevation 57, 58. The mechanism underlyingstatin-associated ALT elevation is still unclear.…”
Section: Clinical Factors Associated With Serum Alt Levelmentioning
confidence: 99%